2004
DOI: 10.1002/cvde.200306270
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Surface Composition and Zeta Potential of Chemical Vapor Synthesized Alumina‐Silica Nanoparticles

Abstract: Ultrafine alumina-silica powders with varying composition gradients within the particles have been produced by chemical vapor synthesis in a hot-wall reactor using the precursors tetraethoxysilane (TEOS) and aluminiumtrisecbutylate (ASB). The surface chemistry at the particle/liquid interface in aqueous dispersions can be adjusted by varying the process parameters. The powders have been characterized by nitrogen adsorption, X-ray diffraction (XRD), transmission electron microscopy (TEM) with local energy dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…The zeta potential approaches nearly asymptotically an isoelectric point (pI) in the neighbourhood of pH 2.7. This pI is in good agreement with values in the vicinity of 2.0-3.0 previously reported for silica powder dispersed in aqueous media [14,15] while Leong [16] has reported that a charge reversal was not observed.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The zeta potential approaches nearly asymptotically an isoelectric point (pI) in the neighbourhood of pH 2.7. This pI is in good agreement with values in the vicinity of 2.0-3.0 previously reported for silica powder dispersed in aqueous media [14,15] while Leong [16] has reported that a charge reversal was not observed.…”
Section: Resultssupporting
confidence: 91%
“…Silica has a particularly low Hamaker constant in water of about 4.3 zJ or $1 kT at 25°C [11]. This means that the van der Waals attraction between silica particles in the flocculated state is very weak compared with most other oxides [15]. Direct force measurements also found short-range repulsive hydration forces for interactions between silica surfaces [21,22].…”
Section: Resultsmentioning
confidence: 96%
“…The composition of individual granules and nanoparticles can be determined by EDX spectrometry. Using these techniques, Sieger et al [55] determined the SiO 2 : Al 2 O 3 ratio in the central and peripheral parts of aluminosilicate microgranules while optimizing the synthesis process.…”
Section: Structure and Physical Propertiesmentioning
confidence: 99%
“…An effective process for the preparation of SiO 2 , Al 2 O 3 , and mixed-oxide particles is vaporization of volatile precursors, followed by thermal decomposition in a reactor [55]. In addition, this process, called the "aerosol" method [56], can be used to produce porous SiO 2 microgranules with a pore size of 8 nm [57].…”
Section: Introductionmentioning
confidence: 99%
“…As nanoparticles exhibit a large specific surface area, it is expected that a change in the surface chemistry will drastically affect the overall characteristics of the powder (e.g., dispersability, corrosion resistance, optical, and electronic properties). Srdic et al [1] as well as Sieger et al [2] used CVS to prepare zirconia and silica particles, respectively, surface doped with alumina and reported the influence of doping on the interface properties in dispersions. The Karlsruhe microwave plasma process (KMP) has been used to apply coatings of oxides (e.g., ZrO 2 ) [3] or polymers (e.g., PMMA) [4] on ceramic nanoparticles.…”
Section: Introductionmentioning
confidence: 98%